GROUND LITTER COEFFICIENT IN FOREST BIOGEOCENOSIS OF POLTAVA-CITY GREEN BELT - Власенко, Н.О. (World of Medicine and Biology, 2013)
There have been cleared up the litter fall and ground litter coefficient (LGC) or intensity index of biological cycle for natural and artificial forests of Poltava-City green belt. It was found out that investigated forests have slow and very slow type of cycling. Interval of intermediate indexes of LGC was 2,07-3,06 for natural forests and 1,92-9,66 for artificial. For softwood and mixed forests specific LGC much higher than for the leafed forests. Index of LGC depends on type of forest and weather conditions.